The Prognostic Significance of the age-adjusted Charlson Comorbidity Index in the Prediction of Postoperative Outcome after Liver Resection for Colorectal Cancer Metastases - Djordjic, Anastasia; Bogdanovic, Professor Aleksandar; Zdujic, Predrag; Djindjic, Uros; Basaric, Dragan; Dugalic, Vladimir (Medical Research, 2024)
Introduction: The prognostic value of the age-adjusted Charlson comorbidity index (ACCI) for patients with colorectal liver metastases (CRLM) undergoing liver resection is still unclear. The aim of this study is to analyze the impact of ACCI in the prediction of short- and long-term outcomes after liver resection in patients with CRLM. Material and methods: Data related to 101 patients who underwent liver resection for CRLM at the University Clinic for Digestive Surgery between October 2019 and October 2022 were analyzed retrospectively. ACCI was determined according to an established point scale. Patients were further divided into two groups: group 1, ACCI <7, and group 2, ACCI ≥7. Results: There was no statistically significant difference in the length of postoperative ICU stay (p=0.9670), semi-ICU stay (p=0.627), and hospital stay (p=0.243). Overall morbidity was higher in group 1 (60%) than in group 2 (39.3), p=0.042, while major morbidity (grade ≥3) was similar between groups, p=0.127. Biliary fistula was more common in group 1 compared to group 2 (12.5% vs 1.6%), p=0.035. In-hospital mortality, 30-day, and 90-day mortality were similar between the study groups (p=1; p=0.517 and p=0.517). During the follow-up period, recurrence was registered in 48.5% of patients. There was no difference in recurrence-free survival between groups, p=0.430. Overall survival was similar between the groups, p=0.141. Conclusion: ACCI can be used to predict postoperative morbidity after liver resection for CRLM. The postoperative mortality and recurrence-free survival are similar regardless of age and comorbidity.